Plant-Based Diet during the Prepubertal Period and Age at Menarche: A Systematic Review - Christanti, Stefani; Syafiq, Ahmad (Jurnal Gizi dan Pangan, 2023)
This systematic review aimed to analyze the effect of a prepubertal plant-based diet, through dietary patterns and its nutritional components, on the age at menarche. Systematic searches through Medline (EBSCO), Embase, Health & Medical Collection (Proquest), Scopus, and Google Scholar for articles published between January 2000 and September 2022 in English using the keywords of plant-based diet, age at menarche, and their synonyms identified 673 articles. Articles were screened through titles and abstracts, as well as full-text reviews based on inclusion/exclusion criteria and assessment of research quality using the JBI Critical Appraisal Tools with a JBI cut-off final score of >50%, leaving 12 articles in this systematic review presented in the PRISMA 2020 flowchart. Data analysis was conducted descriptively by comparing findings between articles. Age at menarche/puberty was reported as an outcome of food intake through a vegetarian diet, Mediterranean diet, vegetable protein, phytoestrogens and isoflavones, and dietary fiber. Based on the analysis of each subgroup, the plant-based diet did not consistently influence the incidence of menarche. In conclusion, a plant-based diet does not significantly affect age at menarche when it is accompanied by a balanced intake of energy and macro-micronutrients. The principles of balanced nutrition and the assistance of nutritionists are needed in practicing a plant-based lifestyle, especially for children and adolescents who are still in the developmental stage.